EDUCATIONAL GAMES PROMOTING FOLK CULTURE THROUGH ARTIFICIAL INTELLIGENCE - Mohapatra, Sarita; Shobana, R.; Amin, Parag; Correa, Frederick Sidney; Saiyad, Fariyah; Srivastava, Richa (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The paper explores the possibilities of educational games that help to encourage, sustain, and disseminate folk culture by giving Artificial Intelligence (AI) support. By integrating Natural Language Processing, Reinforcement Learning, and Computer Vision with Generative AI, the proposed framework will offer adaptive and immersive cultural learning conditions and rely on the actual regional traditions. The design-based method was employed, and it includes cultural data gathering, AI-led personalization, and creation of games to play. Pilot tests in various learning environments showed that there were significant shifts in the interest of the learner, culture knowledge retention and emotional attachment to the folk traditions. Results suggest that AI can be used in stories, adaptive gameplay, and AR-based interactions with culture to make an appreciation of the culture as opposed to the conventional pedagogical methods. The other important aspect brought out in the study is the relevance of the ethical cultural data management and engagement of the community in order to attain authenticity and inclusiveness. On balance, the findings confirm that educational games based on AI can become the scaling and sustainable solution to the reestablishment of the intangible cultural heritage and the enhancement of the contemporary educational process.